1983
DOI: 10.1002/pen.760231704
|View full text |Cite
|
Sign up to set email alerts
|

Azide‐phenolic resin UV resist (MRL) for microlithography

Abstract: Poly(4-vinylphenol) sensitized by an aromatic monoazide compound (4-azidochalcone), called MRL (Micro Resist for Longer wavelengths), has been prepared and evaluated as a negative UV resist. The resist is sensitive to radiation in the 300 to 400 nm region. The sensitivity of MRL is comparable to that of a positive quinonediazide photoresist under exposure to unfiltered light from a high pressure Hg lamp. An aqueous base developer removes the unexposed areas of MRL with no evidence of swelling of the exposed ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The resist comprising poly(vinylphenol) and azide II was named MRL, 3 which is an abbreviation of Micro Resist for Longer wavelength. As seen in Figure 1, this resist strongly absorbs the light in near UV region, especially i line (at 365 nm) of mercury arc.…”
Section: Photoabsorption Spectra Of Resist Filmsmentioning
confidence: 99%
“…The resist comprising poly(vinylphenol) and azide II was named MRL, 3 which is an abbreviation of Micro Resist for Longer wavelength. As seen in Figure 1, this resist strongly absorbs the light in near UV region, especially i line (at 365 nm) of mercury arc.…”
Section: Photoabsorption Spectra Of Resist Filmsmentioning
confidence: 99%
“…The polymer portions of these photoresists from the literature are cyclized polyisoprene, 8 poly(vinylphenol), 9 and polymethyl methacrylate. 10 However, the only commercially available diazide photoactivator was DAS, which has been used with PVP, which is water soluble.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was demonstrated using moleeular beam epitaxy (MBE) to grow very thin (5-36 nm) Be counterdoped layers on n-GaAs (100) (6,7). These studies indicated Sehottky barrier enhancement up to 0.5 eV.…”
Section: Departments Of Electrical Engineering and Materials Science~mentioning
confidence: 86%
“…During our study on negative photoresists consisting of photosensitive aromatic azide compounds and phenolic resins (6,7), azides have been found to decompose in phenolic resin matrices upon heating as well as upon UV exposure (8,9), The main products from thermolysis or photolysis of the azide-phenolic resin composite films are primary and secondary amines which cause the red shift in their UV-visible absorption spectra. The amines * Electrochemical Society Active Member.…”
mentioning
confidence: 99%